1988
DOI: 10.1063/1.340006
|View full text |Cite
|
Sign up to set email alerts
|

Open-tube Zn diffusion in GaAs using diethylzinc and trimethylarsenic: Experiment and model

Abstract: We have characterized the diffusion of Zn into GaAs from the organometallic sources diethylzinc and trimethylarsenic. This method produces surface hole concentrations in excess of 1020 cm−3 with good control of junction depths as shallow as 0.1 μm. Smooth surface morphology is retained. The profile shape is much more complex than the accepted interstitial-substitutional Zn-diffusion model would predict. To explain the observed profiles, a new model for Zn diffusion is proposed and implemented in a computer sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 8 publications
4
20
0
3
Order By: Relevance
“…Figure 9 gives the result of Boltzmann-Ma- tano analysis for the diffusion profile obtained using 11 pieces of Zinc pellets as the diffusion source, the diffusion temperature is 500°C and the diffusion time is 5 h. The rightmost part of Figure 9 where the zinc concentration is very high is not analyzed because that part of the SIMS measurement is not highly reliable. In the subsequent surface region we have [14]. The same results could be obtained for other kink and tail type diffusion profiles in our experiments and literatures.…”
Section: Diffusion Model and Verificationsupporting
confidence: 89%
See 1 more Smart Citation
“…Figure 9 gives the result of Boltzmann-Ma- tano analysis for the diffusion profile obtained using 11 pieces of Zinc pellets as the diffusion source, the diffusion temperature is 500°C and the diffusion time is 5 h. The rightmost part of Figure 9 where the zinc concentration is very high is not analyzed because that part of the SIMS measurement is not highly reliable. In the subsequent surface region we have [14]. The same results could be obtained for other kink and tail type diffusion profiles in our experiments and literatures.…”
Section: Diffusion Model and Verificationsupporting
confidence: 89%
“…The kink-and-tail type profile can also be got from zinc diffusion in GaAs. Bracht and Brotzmann [12,13] simulated the kink-and-tail profiles in GaAs using three kinds of native defects which took part in the different areas, and they thought the near surface kink was a consequence of 0 Ga V and Ga V − controlled dopant diffusion and the profile tail was shaped by the diffusion of 0 Ga I .Reynolds et al [14] also simulated the kink-and-tail profiles from zinc diffusion in GaAs. They first analyzed the zinc concentration profiles using the Boltzmann-Matano method, and got the results that the diffusion coefficient (D) showed different relationship with the zinc concentration (N x , the subscript x is the distance from the surface) in different regions: Table 1 lists the parameters of D i (the diffusion coefficient of…”
mentioning
confidence: 96%
“…Under As-rich conditions, the double-hump Zn profile is obtained in GaAs [1]. In this paper, we found that if Ga atoms were added into the diffusion source, the first hump in Zn profile was "removed".…”
Section: Introductionmentioning
confidence: 72%
“…The shape of Zn profiles has a direct impact on device performance. However, under constant Zn pressure, Zn profiles in III-V semiconductors don't follow the complementary error function [7], distorted phenomenon occurred in Zn profiles [1][2]; it is difficult to predict the precise diffusion profiles. During Zn diffusion process, the self-diffusion of matrix atoms occurred at the same time, thus the self-diffusion should be taken into account during Zn diffusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation